Percutaneous balloon aortic valvuloplasty in the era of transcatheter aortic valve implantation: a narrative review. Issue 2 (7th December 2016) - Keeble, Thomas R; Khokhar, Arif; Akhtar, Mohammed Majid; Mathur, Anthony; Weerackody, Roshan; Kennon, Simon
Abstract : The role of percutaneous balloon aortic valvuloplasty (BAV) in the management of severe symptomatic aortic stenosis has come under the spotlight following the development of the transcatheter aortic valve implantation (TAVI) technique. Previous indications for BAV were limited to symptom palliation and as a bridge to definitive therapy for patients undergoing conventional surgical aortic valve replacement (AVR). In the TAVI era, BAV may also be undertaken to assess the 'therapeutic response' of a reduction in aortic gradient in borderline patients often with multiple comorbidities, to assess symptomatic improvement prior to consideration of definitive TAVI intervention. This narrative review aims to update the reader on the current indications and practical techniques involved in undertaking a BAV procedure. In addition, a summary of the haemodynamic and clinical outcomes, as well as the frequently encountered procedural complications is presented for BAV procedures conducted during both the pre-TAVI and post-TAVI era.